BAHASA DALAM GERBANG FILSAFAT PENDIDIKAN: PERSPEKTIF ONTOLOGI BAHASA DAN BUDAYA - Warami, Hugo (JURNAL TRITON PENDIDIKAN, 2016)
The paper aims to reveal the nature of science sourced from education philosophy through the perspective of language and culture ontology. Genuinely, language is a part of culture; language and culture are two systems independently standing in acquiring the scientific thruth.The current facts show that the curiousity in the perspective of education philosophy has encouraged human beings to admire all things in the nature, even themselves driving Â to the philosophical nature itself. Philosophy grows as human beings ask questions accompanied by admiration and astonishment.Consequently, philosophy begins with desire for questioning. Language on the gate of education philosophy promote language and culture through ontological perspective as a vital part faced by human beings in their whole life. Human beings always create action and reaction which results their dinamic life and forms their existence. Language on the gate of education philosophy can be explored through ontological perspectives including (1) language philosophy domain,(2) education philosophy domain, and (3) language and culture in ontological study.Â